(untitled) (Iranian Journal of Kidney Diseases, 2021)
Introduction. Chronic Kidney Disease (CKD) is of high clinical importance due to cost of outcomes such as kidney transplantation. However, CKD is an overlooked disorder among commercial drivers. The present study aimed to evaluate hypertension and Glomerular Filtration Rate (GFR) among commercial drivers. Methods. In this cross-sectional study, a total of 903 commercial drivers referred for obtaining their health license were recruited. After obtaining informed consent, a questionnaire consisted of demographic characteristics was completed. Blood pressure, level of lipid profile, blood sugar, blood urea nitrogen, and plasma creatinine were measured. Chi-square and independent T-test were used for data analysis. Results. All participants were male. The mean ( ± SD) age and Body mass index were 42 ± (10) years and 27 ± (4) kg/m2, respectively. Of 903 studied cases 40 (4%) had GFR < 60. Increased age and high blood pressure had a significant association with reduced GFR (P < .0001). The ones with sleep apnea were more likely to have GFR < 60, however, the association was not statistically significant after adjusting for related risk factors. Conclusion. Older age and hypertension are considered as risk factors for CKD among commercial drivers. Obstructive sleep apnea also should be kept in mind as a possible risk factor that requires further elucidation and management.